THE IMPLEMENTATION AND HUMAN RIGHT LAW OF POLICY ABOUT STUNTING PREVENTIONIN COVID -19 ERA IN KENDARI: POLICY ABOUT STUNTING PREVENTIONIN COVID -19 - Yunita Amraeni; Toto Surianto; M. Nirwan (STIKes Mandala Waluya Kendari, 2021)
Background.Stunting during the covid period requires policies of handling and prevention in accordance with law and human rights. Therefore, this study aims to determine the prevention strategies and human rights law related stunting to develop the health policy. Method.A qualitative method through in-depth interviews was conducted on 6 informants from the city health office and health centre for strategy and literature study related to human rights and stunting policy law. Results. The results show that there are several strategies that can be prioritized to overcome stunting in the Covid era, such as promotion and support of breastfeeding, Campaign for balanced nutrition and Clean and Healthy Living Behavior (PHBS), Education and counseling using the media, including Short Letter (SMS), or WhatsApp group, Priority services for children under five, through health services and home visits, provision of additional food for malnourished toddlers and pregnant women with chronic energy deficiency, and provision of nutritional supplementation. Conclusion. It is necessary to modify the policy to improve the strategies at the regional level so that stunting can be solved in the pandemic and providing child protection people with stunting an obligation and the joint responsibility of the state, community, family and parents covering juridical protection, economic, social and cultural. Therefore, in fulfilling basic rights child, then the responsibility is carried out holistically by collaborating with the stakeholder.